2010
DOI: 10.1371/journal.pone.0011414
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C: Intravenous Use by Complementary and Alternative Medicine Practitioners and Adverse Effects

Abstract: BackgroundAnecdotal information and case reports suggest that intravenously administered vitamin C is used by Complementary and Alternate Medicine (CAM) practitioners. The scale of such use in the U.S. and associated side effects are unknown.Methods and FindingsWe surveyed attendees at annual CAM Conferences in 2006 and 2008, and determined sales of intravenous vitamin C by major U.S. manufacturers/distributors. We also queried practitioners for side effects, compiled published cases, and analyzed FDA's Advers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
259
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(264 citation statements)
references
References 43 publications
3
259
0
2
Order By: Relevance
“…Infection is one of the most common health problems for which complementary and alternative medicine (CAM) practitioners recommend injection of high doses of ascorbate (reduced vitamin C) (43). One possible reason for the prevalence of this practice is that infection may trigger a systemic inflammatory response that depletes endogenous ascorbate.…”
Section: Vitamin C Depletion and Repletion In Sepsismentioning
confidence: 99%
See 1 more Smart Citation
“…Infection is one of the most common health problems for which complementary and alternative medicine (CAM) practitioners recommend injection of high doses of ascorbate (reduced vitamin C) (43). One possible reason for the prevalence of this practice is that infection may trigger a systemic inflammatory response that depletes endogenous ascorbate.…”
Section: Vitamin C Depletion and Repletion In Sepsismentioning
confidence: 99%
“…However, clinical trial will be necessary to determine the safety of ascorbate in sepsis. Until clinical testing is completed, large doses of ascorbate should not be given to patients with glucose-6-phosphate dehydrogenase deficiency, renal disease, renal insufficiency or renal failure, a history of oxalate nephrolithiasis, or paroxysmal nocturnal hemoglobinuria (43).…”
Section: Vitamin C Dosage and Safetymentioning
confidence: 99%
“…Parenteral vitamin C has been administered by physicians for many decades, primarily as an alternative therapy for cancer and viral infections [1] . Patients typically receive doses of ~28 g vitamin C per treatment, on average once every four days [1] .…”
Section: Introductionmentioning
confidence: 99%
“…Patients typically receive doses of ~28 g vitamin C per treatment, on average once every four days [1] . We and others have shown that parenteral vitamin C is an effective therapy for cancer-and chemotherapy-related fatigue [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the same dose had no effect on patient well-being and survival in two double-blind placebo-controlled trials, and AA was discarded as a treatment modality [6] [7]. Recent clinical evidence, however, indicates that the role of AA in cancer treatment should be examined anew [8]. The originally reported observational studies used IV and oral AA, but the subsequent doubleblind placebo-controlled studies used only oral AA.…”
Section: Introductionmentioning
confidence: 99%